IMPLEMENTASI CUSTOMER-BASED BRAND EQUITY MODEL DALAM MENINGKATKAN PEMANFAATAN PELAYANAN KESEHATAN DI PUSKESMAS SUNGAI RAMBUTAN, KABUPATEN OGAN ILIR, 2011 - Iwan Stia Budi; A. Fickry Faisya (Fakultas Kesehatan Masyarakat, Universitas Jember, 2012)
Purpose of study was formulate recommendation to improving the utilization of Sungai Rambutan Public Health Center through Customer-Based Brand Equity Model. This study used descriptive study. Result : Brand awareness about sungai rambutan: Sungai Rambutan public health center as free health services, health services no reliable, no guarantee of healing, infrastructure incomplete ,the discipline of work less and not had willingness to visit sungai rambutan public health center if they were sick.